Pengetahuan Wanita Usia Subur Tentang Dampak Pernikahan Dini Terhadap Kehamilan Di Kecamatan Rambah Hilir - Elvira junita, Elvira Junita; Tika, Pebri; Ermiza, Ermiza; Heny Sepduwiana, Heny Sepduwiana (Maternity and Neonatal : Jurnal Kebidanan, 2022)
During the third trimester of pregnancy, pregnant women often experience a sense of discomfort with physiological changes in themselves, so it is only natural for pregnant women in the third trimester to experience difficulties during activities. The problem that is often encountered in third trimester pregnant women is swelling in the legs caused by fluid accumulation or what is often referred to as edema in third trimester pregnant women. Considering the discomfort of pregnant women in the third trimester, extra program strategies and activities that are more innovative are needed, one of which is by giving massage using the foot massage method. This foot massage method is effective in reducing the depth of edema. The purpose of this study was to determine the relationship between foot massage and the degree of edema in third trimester pregnant women in Rambah Village, Rambah Hilir District. The type of research used is Pre Experiment with One Group Pretest Posttest approach. The sample in this study was all 15 pregnant women in the third trimester who experienced edema with a purposive sampling technique containing several criteria. The research measuring instrument used is a checklist sheet. The statistical test used is the t-dependent test. The results showed that the difference in the average depth of edema before (pre-test) and after (post-test) given foot massage was 2.27. The results of statistical tests obtained p value = 0.0001 (p <0.05), it can be concluded that there is a significant difference in the depth of edema before being given foot massage and after being given foot massage. It is hoped that third trimester pregnant women can understand the benefits of foot massage and increase knowledge and be able to apply it. Keywords : Foot Massage, Edema, Third Trimester Pregnant Women